Simulation Dominated Approach versus Video Dominated Approach in Teaching Consecutive Interpreting to Undergraduates: An Exploratory Comparison Study - Li, Xiangdong (Onomázein, 2019)
Video dominated instruction (VDI) and simulation dominated instruction (SDI) are commonly practised in interpreter training, and yet their teaching effects have not been adequately researched so far. The present study was intended to compare the effectiveness of the two instructional approaches in teaching consecutive interpreting (CI) to third-year undergraduates. A quasi-experimental two-group pre-test/post-test comparison design was used. Sixty-two students took a pre-test on consecutive interpreting skills and completed a pre-self-assessment to rate their competence in eleven learning objectives at the beginning of a consecutive interpreting course. Thirty-one students in class one as the comparison group received VDI, while thirty-one students in class two received SDI. Sixteen weeks later at the end of the course, the two classes took a post-test on consecutive interpreting skills and completed a post-self-assessment to rate their competence in the same eleven learning objectives. After controlling the effects of pre-test and pre-self-assessment scores, ANCOVA results suggested that VDI and SDI are equally effective in teaching CI to undergraduates, except for one aspect that the latter is more effective in cultivating students’ ability to use non-verbal elements. Pedagogical implications about the complementary nature of the two approaches were discussed.